Cyto-Histological Evaluation of Bronchial Brushing, Bronchial Washing and Bronchial Biopsy in Lung Tumours: A Prospective Study From Tertiary Care Centre in Southern Rajasthan - Joshi, Jigyasu; Bhargava, Sunita (Annals of Pathology and Laboratory Medicine, 2020)
Background: Lung cancer is the most frequently diagnosed major cancer in the world with a high mortality rate because most of the cases are diagnosed in advanced stage therefore early diagnosis of lung cancer is crucial in management. Examination of specimens obtained through flexible fiberoptic bronchoscope is an important and often the initial diagnostic technique performed in patients with suspected lung carcinoma. A study on cyto histological evaluation of bronchoscopic procedure samples was carried out to find out the efficacy of the procedures in lung tumours in southern Rajasthan. Methods: Bronchoscopy was performed in total 100 patients with clinico- radiological suspicion of lung cancer. Bronchial brushing, washing and biopsy were taken wherever possible. Cytology and biopsy samples processed and slides prepared for examination. Result: Overall sensitivity and specificity of bronchial brushing was 85.3% and 56.25% while for wash/BAL (bronchoalveolar lavage) the values were 78.34% and 59.26% respectively. Bronchial brushing had higher sensitivity for central as well as peripheral tumours while wash/BAL had higher sensitivity as well as specificity for peripheral tumours. Conclusion: Bronchial brushing and wash/BAL has excellent sensitivity and good specificity and yields almost same information as biopsy. But regarding histological typing of lesions, biopsy is more effective than cytological study. Therefore, all these techniques may be used concurrently to diagnose the lung tumours.